Electronic health record : a systems analysis of the medications domain - Scarlat, Alexander; Halamka, John. (Boca Raton : Taylor & Francis, 2012)
"This book introduces readers to structured systems analysis and the medications domains. It starts off with top-down decomposition of workflows and data. It applies structured systems analysis methodology and tools to electronic prescription, computerized physician order entry, drug dispensation, medication administration, and clinical decision support. Providing a comprehensive view of the EHR/EMR, the text covers user interface considerations, reporting requirements, and standards and vocabularies for meaningful use. Assuming no previous clinical and/or informatics knowledge, the author uses accessible language and includes over 250 figures and 100 review questions with answers"--Provided by publisher.
"A Productivity Press Book."
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Medical records -- Data processing; Electronic books